2005
DOI: 10.1007/s10672-005-6939-5
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Performance of Indian Firms: The Effect of Board Size and Ownership

Abstract: The paper reviews international literature on corporate governance and firm performance and investigates the relationship in the Indian context, taking into account the endogeneity in the relationship. Governance parameters include board size, directors' shareholding, institutional and foreign shareholding, while the fragmentation in shareholding is captured by public shareholding. A simultaneous equation regression model for Tobin's Q, as a measure of firm performance, is attempted using these variables, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
122
3
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(148 citation statements)
references
References 34 publications
15
122
3
4
Order By: Relevance
“…Based on the empirical results of the analysis researcher has to reject H3 and H4 since there are an insignificant positive relationship between board independence and performance measures. These results consistence with the previous findings of (Jackling & Johl, 2009;Dwivedi & Jain, 2005).…”
Section: 2empirical Resultssupporting
confidence: 93%
“…Based on the empirical results of the analysis researcher has to reject H3 and H4 since there are an insignificant positive relationship between board independence and performance measures. These results consistence with the previous findings of (Jackling & Johl, 2009;Dwivedi & Jain, 2005).…”
Section: 2empirical Resultssupporting
confidence: 93%
“…However, authors also observed that board size below six has no effect on performance. It's viable for only large size board (more than seven) Diwedi & Jain (2002), conducted a study on 340 large, listed Indian firms for the period 1997-2001. This study found a weak positive relation between board size and performance of the firm.…”
Section: Prior Studies On Board Size and Financial Performancementioning
confidence: 99%
“…Some studies (Mak & Yuanto, 2003;Haniffa & Hudaib, 2006;Garg, 2007) favor smaller board sizes. However, (Abidin et al, 2009) and Sulong & Nor, 2010) favor large board sizes, (Dwivedi & Jain, 2005;Jackling & Johl, 2009) support large board size. Francoeur et al (2012) asserted that large shareholders have strong incentives to manage earnings upward prior to stockfinanced transactions to limit the dilution of their controlling position.…”
Section: The Literature Reviewmentioning
confidence: 99%